The Zulu War - Clammer, David (London : Pan Books, 1975)
"The book places the conflict in its political context, and deals in detail with the military aspects of the campaign. It is based on a wide range of sources, including official accounts and memoirs of eye-witnesses and participants, early histories of the war and more recent studies. Maps and illustrations add to the value of a study of interest to historians of military affairs and of the nineteenth century generally."--AntiquarianAuctions.
The way to war -- The invasion -- Isandhlwana -- The defence of Rorke's Drift -- The right flank column -- The left flank column -- Hlobane and Kambula -- The relief of Eshowe -- Reorganization -- The prince imperial -- Ulundi.
Originally published: Newton Abbot : David and Charles, 1973.
Includes bibliographical references (pages 197-200) and index.
Keywords: 1879; Zulu War, 1879.; Guerre des Zoulous, 1879.; Zulu War